Aktivisme Gerakan Wanita Indonesia (Gerwani) di Bali Tahun 1956-1965 - Erawan, I Ketut Putra; Amirah, Ufiya; Pramana, Gede Indra (Jurnal Nawala Politika, 2023)
This study aims to explain about Gerwani's activism for the rights of the people, especially Baliness women in 1956-1965. The end of Soekarno's era democratic regime, also ended the greatness of the left political wing in Indonesia. Communist forces were destroyed down to the grassroots, including Gerwani. Gerwani's contribution to building the nation, especially their participation in struggling for women's rights, has disappeared, and has not been written down in Indonesian's history. To further discuss these activities, the researcher uses theory of M arxist feminism by Lise Vogel , and is supported by the conceptual framework of activism and socialist feminist movements. Th e research method used is a qualitative research method based on literature study. This research found that Gerwani Bali's activism in 1956-1965 included struggles in the sector of political - economy and socio-cultural action. In the political-economic sector , Gerwani Bali has participated in the struggle for land policy reform. And in social-cultural action, Gerwani Bali built Melati kindergartens, child care foundations in markets, art education centers, and advocated for sexual violence cases in Badung. Keywords: Gerwani Bali, Activism, Socialist Feminist Movement.